How Do Exchanges Select Stocks for Option Listing? - Mayhew, Stewart; Mihov, Vassil (Journal of Finance, 2004)
ABSTRACT We investigate the factors influencing the selection of stocks for option listing. Exchanges tend to list options on stocks with high trading volume, volatility, and market capitalization, but the relative effect of these factors has changed over time as markets have evolved. We observe a shift from volume toward volatility after the moratorium on new listings ended in 1980. Using control sample methodology designed to correct for the endogeneity of option listing, we find no evidence that volatility declines with option introduction, in contrast to previous studies that do not use control samples.